Analisis Pengaruh Harmonisa Transformator Distribusi 2500 kVA - Melkias, Alvera Apridalianti; Indriyani, Indriyani; Hidayat, Taufik (Fakultas Teknik UMRI, 2025)
The high harmonic content in the electrical load or in the power distribution system can result in worse power quality, lower system power factor, distorted system voltage waveform, increased power losses in the system, overheating of the transformer, and inefficient use of electrical energy. So that it can reduce the efficiency of the transformer. The purpose of this study is to analyze the effect of harmonics on a distribution transformer with a capacity of 2500 kVA using a quantitative data collection method, namely primary and secondary data collection. This study offers an integrated approach that includes harmonic measurements and analysis of direct impacts on the efficiency of a 2500 kVA distribution transformer in the context of the automotive industry, which has not been widely reported in the national literature. Based on the results of measurements and calculations on the transformer, the Total Harmonic Distortion Current (THDI) value is + 9% which exceeds the permissible value of 8% while the Total Harmonic Distortion Voltage (THDV) value is + 2% in accordance with the permissible limit of 5%. The analysis results obtained that due to the presence of harmonics in the electrical distribution system, the distribution transformer experienced a decrease in its efficiency value by 2%, which was originally without harmonics the transformer efficiency was 98.8% and due to the presence of harmonics the transformer efficiency became 96.8%. The combination of real-time harmonic measurements and calculations in the industry not only offers technical advantages, but also strategically supports efficiency, reliability of the electrical system, and smarter data-based decision making.